Sportfinanzierung - Spannungen zwischen Markt und Staat - Büch, Martin-Peter; Maennig, Wolfgang; Schulke, Hans-Jürgen (Edition HWWI, 2008)
On the one hand, sport like any other activity in society is burdened with public taxes, and on the other hand, in comparison to similar activities, is tax-free and even publicly supported. This ambivalence of tax treatment of sport has repeatedly raised questions about the public financing of sport: To what extent are services provided by the public sector justified, and to what extent do sporting events trigger taxation? This volume, edited by Hans-Peter Büch, Wolfgang Maennig and Hans-Jürgen Schulke, attempts to answer selected questions on this problem from a scientific and sports-political point of view under the motto "Science meets Practice".